Photoluminescence properties of cerium oxide nanoparticles as a function of lanthanum content - Deus, R. C. [UNESP]; Cortés, J. A. [UNESP]; Ramirez, M. A. [UNESP]; Ponce, M. A.; Andres, J. [UNESP]; Rocha, L. S.R. [UNESP]; Longo, E. [UNESP]; Simões, A. Z. [UNESP] (Elsevier, 2015)
Abstract The structural and photoluminescent properties at room temperature of CeO2 and La-doped CeO2 particles were undertaken. The obtained particles were synthesized by a microwave-assisted hydrothermal method (MAH) under different lanthanum contents. X-ray diffraction (XRD), Fourier transform infrared (FT-IR), Fourier transform Raman (FT-Raman), Ultra-violet spectroscopy (UV-vis) and photoluminescence (PL) measurements were carried out. XRD revealed that the powders are free of secondary phases and crystallize in the cubic structure. Raman data show that increasing La doping content increase oxygen vacancies due to lattice expansion. The UV/vis absorption spectroscopy suggested the presence of intermediate energy levels in the band gap of structurally ordered powders. Lanthanum addition creates oxygen vacancies and shifts the photoluminescence in the low energy range leading to intense PL emission.
Keywords: Ceramics; Crystal growth; Luminescence; Nanostructures; X-ray diffraction